PENGARUH MANAJEMEN KELAS MAKE EVERY MINUTE COUNT TERHADAP KEAKTIFAN BELAJAR SISWA KELAS IV DI MI TAUFIQURRAHMAN 2 KUKUSAN - Cecep Maman Hermawan; Okta Rosfiani; Rani Sheilla; Siti Nur Elizah; Putri Ratu Bilqis El-Amini; Sulthan Hawari (Pengembangan Pendidikan dan Pembelajaran Sekolah Dasar, 2024)
The Make Every Minute Count (MEMC) pattern is the focus of classroom management implementation which is considered effective in designing educational experiences that encourage active participation in student learning, so that it is in line with the purpose of this research through the involvement of 42 MI Taufiqurrahman 2 Steamer students as samples divided into control classes and experiments (purposive sampling) from 457 research results by applying through methods quasi-experiment. In testing samples using questionnaires as the main instrument, the feasibility test results of the instrument 0.836 (Cronbach's Alpha) are known. The population variance of the two homogeneous class groups is seen from the comparison of t-count and t-table (0.198 > 0.05). The post-test MEMC (Experiment) result of 86.00 is greater than the post-test Classroom Meeting (Control) of 82.29. The meaning of the results of this test proves that MEMC class management affects student learning activity in MI Taufiqurrahman 2 Kukusan. The results of these findings, contributing to realizing classroom management oriented to student learning activity, but its effectiveness may not be generalizable to students outside the sample subjects studied.